BENTUK PENYAJIAN GONDANG BOROGONG PADA UPACARA PERKAWINAN DI PASIR PENGARAIAN KABUPATEN ROKAN HULU-RIAU - Lia Wardani (JURNAL PENDIDIKAN ROKANIA, 2016)
This study aims to determine of presentation Gondang Borogong on marriage in Pasir Pengaraian kabupaten Rokan Hulu Riau. The Type of research is qualitatifresearch with data processing in the form descriptive analysis. The object of this study is the art group Gondang Borogong name kubu manggis used in thewedding ceremony by Mr.Amrizal. Gondang Borogong from of presentation is a percussion ensemble music, displayed on custom event, such as wedding ceremonies, welcoming guest grand, pencak silat and traditional events.